Kinetics and Mechanism of Chlorination of N-Acetylglycin by Chloramine-T In Acidic Medium - Noor Saeed (College of Education for Pure Sciences, 1999)
ABSTRACT The kinetics of chlorination of N-acetylglycin (AG) with sodium N-chloro -p- toluene sulphonamide (CAT) in presence of HCL has been studied at 318 oK. The reaction rate shows afirst -order dependence each on [CAT] and [H+] and zero order dependence on [AG]. The Variation of ionic strength of the medium or chloride ion had no significant effect on the reaction rate. Addition of P-TSA is marginally affected the reaction rate. The rate increase with decreasing dielectric constant of the medium. The stiochiometry of the reaction was found 1:1 and the oxidation producte were identified. The thermodynamic parameters were computed. The mechanism proposed and the derived rate law were in agreement with the observed kinetics.